(3GdGbJUGOjGJ GdfGejI CReGJ hMdhd (B/s - (3GdYWjI, YHO GdMSjf hGOjs ((3YeGf(B: s (3OGQ GdTQhb ddfTQ hGdJhRjY(B, s, 2001)
(3GdfXGe GdGbJUGOj GdYGdej GdLOjO hedGeM GdacQ GdGbJUGOj GdeYGUQ,GdNUNUI aj GdHdOGf GdfGejI(B:(3EjLGHjGJgG hSdHjGJgG,GdYhdeI hGdBKGQ GdSdHjI dgG,GdTQGcI GdYGOdI Hjf GdHdOGf GdeJbOeI hGdHdOGf GdfGejI cMd eecf dUGdM GdWQajf,ebJQM GSJQGJjLj dJMbjb GdJfejI GdGbJUGOjI aj GdHdOGf GdfGejIs
(3HHdjhZQGajG(B:(3U(B.233-234(3; GdedGMb(B:(3U(B.235-280s
Keywords: (3GdGbJUGO GdJMdjdjs; (3GdJfejI GdGbJUGOjIs; (3GdYhdeIs